High Circulating Methylated DNA Is a Negative Predictive and Prognostic Marker in Metastatic Colorectal Cancer Patients Treated With Regorafenib - Amatu, Alessio; Schirripa, Marta; Tosi, Federica; Lonardi, Sara; Bencardino, Katia; Bonazzina, Erica; Palmeri, Laura; Patanè, Damiano Alfio; Pizzutilo, Elio Gregory; Mussolin, Benedetta; Bergamo, Francesca; Alberti, Giulia; et al. (Frontiers in Oncology, 2019)
Background: Regorafenib improves progression free survival (PFS) in a subset of metastatic colorectal cancer (mCRC) patients, although no biomarkers of efficacy are available. Circulating methylated DNA (cmDNA) assessed by a five-gene panel was previously associated with outcome in chemotherapy treated mCRC patients. We hypothesized that cmDNA could be used to identify cases most likely to benefit from regorafenib (i.e. patients with PFS longer than 4 months). Methods: Plasma samples from mCRC patients were collected prior to (baseline samples N=60) and/or during regorafenib treatment (N=60) for the assessment of cmDNA and total amount of cell free DNA (cfDNA). Results: In almost all patients, treatment with regorafenib increased the total cfDNA, but decreased cmDNA warranting the normalization of cmDNA to the total amount of circulating DNA (i.e. cmDNA/ml). We report that cmDNA/ml dynamics reflects clinical response with an increase in cmDNA/ml associated with higher risk of progression (HR for progression=1.78 [95%CI: 1.01-3.13], p=0.028). Taken individually, high baseline cmDNA/ml (above median) was associated with worst prognosis (HR for death=3.471 [95%CI: 1.83-6.57], p<0.0001) and also predicted shorter PFS (<16 weeks with PPV 86%). In addition, high cmDNA/ml values during regorafenib treatment predicted with higher accuracy shorter PFS (<16 weeks with a PPV of 96%), therefore associated with increased risk of progression (HR for progression =2.985; [95%CI: 1.63–5.46; p<0.0001). Conclusions: Our data highlight the predictive and prognostic value of cmDNA/ml in mCRC patients treated with regorafenib.